Penerapan Model Pembelajaran Interaktif (Model Pembelajaran Berdasarkan Masalah dan Pembelajaran Kooperatif Tipe Group Investigation ) terhadap Keterampilan Proses Sains pada Perkuliahan Ilmu Kealaman Dasar Mahasiswa PGSD UM Palangkaraya - Rita Rahmaniati; Fathul Zannah; Fazakkir Noor (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
Basic Science lecture with a value of t-test value of 4.714 is greater than t-table value of 2.010635 and Problem Based Learning Model can improve cognitive learning outcomes of students on all the indicators of the indicator 1 (formulating the problem) from 0.60 to 0.78, the indicator 2 (formulating hypotheses) of 0.78 into 0.86, indicator 3 (create tables of data) from 0.18 to 0 , 36, indicator 4 (make a line graph) of 0.54 and 0.20 into a 5 indicator (draw conclusions) from 0.60 to 0.80. In addition the Cooperative Learning Model Groupo investigation type can’t improve student learning outcomes in the cognitive processes of nature Basic Science lecture significantly due to the value of -1.53144 t-count is smaller than t-table value of 2.032244. But the use of cooperative learning model group investigation type can improve learning outcomes 3 indicators of cognitive process in which the indicators 2 (hypothesis formulation) which increased from 0.17 to 0.36, indicator 3 (table creation) which increased from 0.44 becomes 0.61 and indicator 4 (graphing) which increased from 0.72 to 0.80. When seen from the comparison of the two models used the results showed that there are differences in the cognitive processes of learning outcomes of students in the course of nature basic science lecture between learning model Problem Based Learning and Cooperative Learning with group investigation type t value of 3.967 rely more than t table that is equal to 2.019541.